Use of unmanned vehicles in search and rescue operations in forest fires: Advantages and limitations observed in a field trial. (September 2015) - Karma, S.; Zorba, E.; Pallis, G.C.; Statheropoulos, G.; Balta, I.; Mikedi, K.; Vamvakari, J.; Pappa, A.; Chalaris, M.; Xanthopoulos, G.; Statheropoulos, M.
Abstract: Search and Rescue (SaR) in forest fires is usually applied in a broad area, under foggy or smoky conditions. It mostly involves location of entrapped fire crew or people in between fire fronts, as well as, safely removing them away from the dangerous zone. Moreover, SaR is applied in evacuation of rural residential areas due to heavy smoke impacts, or fire front approaching. Experiences achieved during a field trial, in which unmanned aerial and ground vehicles were deployed and used in a simulated forest fire SaR scenario, are presented. For planning and running the field trial a number of parameters were taken into consideration; logistics, safety plan, contingency plan, different agencies cooperation, time frames and ethical issues. Advantages of using unmanned aerial and ground vehicles in SaR operations include capability of planning and monitoring the operations, integration with the manned resources, connectivity with command and control centers, as well as, coordination of the different unmanned aerial and ground vehicles' platforms. Significant increase of personnel safety is possible through the capabilities of air quality monitoring and search over dangerous areas. Current limitations include limited heat resistance of vehicles and limited flying capability in strong winds and turbulence. Failure of communications is also possible due to rough terrain (autonomy limitations). Against all the limitations, a number of unmanned vehicles already exist that can be adapted successfully for SaR operations in forest fires.